1995
DOI: 10.1152/ajprenal.1995.268.5.f899
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal alkalinization reduces Jmax and Km of albumin receptor-mediated endocytosis in OK cells

Abstract: In this study, we investigated the effects of endosomal alkalinization on kinetics of endocytotic uptake in intact proximal tubule-derived opossum kidney cells. We used fluorescein isothiocyanate (FITC)-labeled albumin and FITC-dextran as endocytotic substrates for receptor-mediated endocytosis and fluid-phase endocytosis, respectively. The pH in endosomes labeled with either FITC-albumin or FITC-dextran rose in the presence of the vacuolar-type ATPase inhibitor, bafilomycin A1, and in the presence of NH4Cl. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 0 publications
4
84
1
Order By: Relevance
“…Bafilomycin Al and methylamine were able to abolish this punctate staining, consistent with their ability to inhibit acidification of intracellular organelles (Williamson and Neale, 1994;Gekle et al, 1995;Lencer et al, 1995 we conclude that retention of excitatory amino acid neurotransmitters within granule cell synaptic yesides is dependent on the continual maintenance of rather than L~pH 5. These requirements for acidic amino acid retention are identical to those previously reported for endogenous glutamate exocytosis from cerebrocortical synaptosomes (S ánchez-Prieto et al, 1987) and confirm the primary role of~in the uptake and retention of acidic amino acids within synaptic vesicles (Maycox et al, 1988;Tabb et al, 1992).…”
Section: Synaptic Vesicle Recycling Does Not Require Lumenal Acidificsupporting
confidence: 73%
See 1 more Smart Citation
“…Bafilomycin Al and methylamine were able to abolish this punctate staining, consistent with their ability to inhibit acidification of intracellular organelles (Williamson and Neale, 1994;Gekle et al, 1995;Lencer et al, 1995 we conclude that retention of excitatory amino acid neurotransmitters within granule cell synaptic yesides is dependent on the continual maintenance of rather than L~pH 5. These requirements for acidic amino acid retention are identical to those previously reported for endogenous glutamate exocytosis from cerebrocortical synaptosomes (S ánchez-Prieto et al, 1987) and confirm the primary role of~in the uptake and retention of acidic amino acids within synaptic vesicles (Maycox et al, 1988;Tabb et al, 1992).…”
Section: Synaptic Vesicle Recycling Does Not Require Lumenal Acidificsupporting
confidence: 73%
“…In nonneuronal constitutive membrane traffic, vesicle acidification is primarily associated with protein processing, degradation, and targeting rather than the mechanism of vesicle traffic itself. Thus, bafilomycin Al pretreatment does not inhibit fluid-phase endocytosis into kidney cells (Gekle et al, 1995), or the attachment or uptake by receptor-mediated endocytosis of retroviruses (Martinez et al, 1996), clostridial neurotoxins (Simpson et al, 1994;Williamson and Neale, 1994), or transferrin (Johnson et al, 1993;van Weert et al, 1995). V-ATPase inhibition does, however, inhibit activation or dissociation of these agents from their receptors in a pH-dependent step after endocytosis has taken place.…”
Section: Synaptic Vesicle Recycling Does Not Require Lumenal Acidificmentioning
confidence: 99%
“…Albumin endocytosis was reported to be decreased by extracellular hypertonicity, which interferes with the formation of clathrin lattice, thus inhibiting the formation of clathrin-coated pits (72). Gekle et al also reported that alkalinization of endosomes by the addition of NH 4 Cl or bafilomycin A 1 to opossum kidney cells in vitro reduced the receptor-mediated endocytosis of albumin but did not affect fluid-phase endocytosis of dextran (73). The same group described reduced endocytosis of albumin by cytochalasin D, which disrupts the actin cytoskeleton, and by nocodazole, which interferes with microtubule formation (72).…”
Section: Reduction Of Renal Uptakementioning
confidence: 97%
“…To investigate whether CLC5 is localized in endosomes, we used fluoresceinlabeled albumin and dextran as putative markers of the receptor-mediated and fluid-phase endocytotic pathway, respectively (14,38), and fluorescein-labeled ricin as a putative panendosomal marker (39). LLC-PK1 cells transfected with FLAGtagged rCLC5 were exposed to each of these fluorescent markers at their apical surface over a sufficient length of time for them to be entrapped in apical membrane early endosomal vesicles and were then fixed, stained with the FLAG primary antibody and a Texas-red-conjugated secondary antibody, and visualized by confocal microscopy.…”
Section: Fig 4 Immunodetection Of Clc5 Proteins In Denaturing Polyamentioning
confidence: 99%
“…It has been postulated that CLC5 may provide an electrical shunt to dissipate the potential gradient across the endosomal membrane generated by electrogenic proton transport into the endosomal lumen. Thus, loss of CLC5 function would be predicted to impair endosomal acidification, which is normally required for endocytosis (14), trafficking to lysosomes (15), and recycling back to the surface (16). In this model, low molecular weight proteinuria in Dent's disease occurs because of failure of endocytosis from the proximal tubule lumen, which is the normal pathway for reabsorption of low molecular weight proteins (17).…”
mentioning
confidence: 99%